A Persuasive Technology for Managing Waste Disposal through Smart Trash Bin and Waste Disposal Tracker - Oscar Karnalim; Oscar Wongso; Vincent Elbert Budiman; Felix Christian Jonathan; Bertha Alan Manuel; Marlina Marlina (International Journal on Information and Communication Technology (IJoICT), 2020)
Waste management issue is a relevant topic that had been focused on many persuasive technologies. This issue is not only related to getting disposed of waste in proper places but also reducing waste disposal volume. This paper proposes a persuasive system that aims both goals by providing a smart trash bin and waste disposal tracker. The smart trash bin is an IoT-featured trash bin whereas waste disposal tracker is a mobile application which can record user daily waste disposal volume statistic. Based on the evaluation, our proposed system has achieved both goals. Additionally, it also solves several impediments such as incapability of moral background to encourage people to dispose waste on the trash bin, boring and monotonous waste disposal activity, and discouragement for disposing waste due to full trash bin. In order to attract people, our system includes attractive mechanisms such as playful experience, reflective experience, and gamification. Playful experience is applied to a smart trash bin, whereas the other two are applied to the waste disposal tracker.